Communicating Uncertainty in Written Consumer Health Information to the Public: Parallel-Group, Web-Based Randomized Controlled Trial - Büchter, Roland B; Betsch, Cornelia; Ehrlich, Martina; Fechtelpeter, Dennis; Grouven, Ulrich; Keller, Sabine; Meuer, Regina; Rossmann, Constanze; Waltering, Andreas (JMIR Publications, 2020)
BackgroundUncertainty is integral to evidence-informed decision making and is of particular importance for preference-sensitive decisions. Communicating uncertainty to patients and the public has long been identified as a goal in the informed and shared decision-making movement. Despite this, there is little quantitative research on how uncertainty in health information is perceived by readers. ObjectiveThe aim of this study was to examine the impact of different uncertainty descriptions regarding the evidence for a treatment effect in a written research summary for the public. MethodsWe developed 8 versions of a research summary on a fictitious drug for tinnitus with varying degrees (Q1), sources (Q2), and magnitudes of uncertainty (Q3). We recruited 2099 members of the German public from a web-based research panel. Of these, 1727 fulfilled the inclusion criteria and were randomly presented with one of these research summaries. Randomization was conducted by using a centralized computer with a random number generator. Web-based recruitment and data collection were fully automated. Participants were not aware of the purpose of the study and alternative presentations. We measured the following outcomes: perception of the treatment effectiveness (primary), certainty in the judgement of treatment effectiveness, perception of the body of evidence, text quality, and intended decision. The outcomes were self-assessed. ResultsFor the primary outcome, we did not find a global effect for Q1 and Q2 (P=.25 and P=.73), but we found a global effect for Q3 (P=.048). Pairwise comparisons showed a weaker perception of treatment effectiveness for the research summary with 3 sources of uncertainty compared to the version with 2 sources of uncertainty (P=.04). Specifically, the proportion of the participants in the group with 3 sources of uncertainty that perceived the drug as possibly beneficial was 9% lower than that of the participants in the group with 2 sources of uncertainty (92/195, 47.2% vs 111/197, 56.3%, respectively). The proportion of the participants in the group with 3 sources of uncertainty that considered the drug to be of unclear benefit was 8% higher than that of the participants in the group with 2 sources of uncertainty (72/195, 36.9% vs 57/197, 28.9%, respectively). However, there was no significant difference compared to the version with 1 source of uncertainty (P=.31). We did not find any meaningful differences between the research summaries for the secondary outcomes. ConclusionsCommunicating even a large magnitude of uncertainty for a treatment effect had little impact on the perceived effectiveness. Efforts to improve public understanding of research are needed to improve the understanding of evidence-based health information. Trial RegistrationGerman Clinical Trials Register DRKS00015911, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00015911 International Registered Report Identifier (IRRID)RR2-10.2196/13425